Topical 5% tranexamic acid for the treatment of melasma in Asians: A double-blind randomized controlled clinical trial - Pinyapat Kanechorn Na Ayuthaya (2018)
Background: Topical tranexamic acid has been claimed to lighten melasma without serious adverse effects. However, controlled studies assessing the efficacy and safety of topical tranexamic acid (TA) for the treatment of melasma is limited. Objective: To assess in a double blind, randomized, prospective study, the efficacy of topical 5% tranexamic acid versus vehicle for treatment of melasma. Methods: Twenty-three women with bilateral epidermal melasma enrolled in a split-face trial lasting 12 weeks. Patients blindly applied topical 5% tranexamic acid and its vehicle, to the designated sides of the face twice daily in addition to the assigned sunscreen each morning. Pigmentation and erythema were measured objectively using a mexameter and Melasma Area and Severity Index (MASI), in addition to physician and patient global assessments. Results: Twenty-one patients completed the study. Eighteen out of twenty-three patients (78.2%) showed decrease in the melanin index on either or both sides of the face by the end of 12 weeks compared to baseline. The MASI scores were also significantly reduced on both tested sides. However, lightening of pigmentation induced by TA gel was neither superior nor different (p >0.05) compared to its vehicle although erythema was significant on the TA-applied site (p <0.05). Conclusions: Although lightening of pigmentation was obtained, the results were not significant between the two regimens. However, topical TA produced erythema. © 2012 Informa UK, Ltd.